Risk Evaluation in Providing Gold Credit at PT Pegadaian Medan Sunggal Branch - Citra Astuti; Muhammad Rizki Aulia; Sri Mulyani (Journal of Innovative and Creativity, 2026)
Gold loans are one of PT Pegadaian's flagship products, playing a crucial role in meeting the public's financing needs with gold as collateral. Despite their relatively high level of security, gold loans still carry various risks, such as credit risk, the risk of gold price fluctuations, and operational risk. Therefore, risk evaluation in gold loans is crucial to ensure smooth operations and maintain the company's financial performance. This study aims to evaluate the risks involved in the gold loan disbursement process at PT Pegadaian's Medan Sunggal Branch and identify the risk control easures implemented. This study used a descriptive qualitative approach, collecting data through interviews, observation, and documentation. The research informants consisted of branch managers and employees directly involved in the gold loan disbursement process. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that the main risks in gold loans at PT Pegadaian's Medan Sunggal Branch include credit risk due to late customer payments, the risk of gold price fluctuations that can affect the collateral value, and operational risks related to the appraisal and administration processes. However, PT Pegadaian Medan Sunggal Branch has implemented various risk management strategies, including gold valuation standards, strict operational procedures, and regular credit monitoring. This research is expected to provide evaluation material and input for management in improving the effectiveness of gold credit risk management.